Barriers and facilitators to more timely treatment of aneurysmal subarachnoid haemorrhage across two tertiary referral centres in Australia: A thematic analysis. (September 2022) - Nguyen, Thuy Phuong; Stirling, Christine; Kitsos, Gemma; Nichols, Linda; Chandra, Ronil V.; Rehman, Sabah; Smith, Karen; Mosley, Ian; Lai, Leon; Asadi, Hamed; Dubey, Arvind; Froelich, Jens; et al.
Abstract: Background: Delays in treatment of aSAH appear to be common but the causes are not well understood. We explored facilitators and barriers to timely treatment of aSAH. Methods: We used a multiple case study with cases of aSAH surviving> 1 day identified prospectively. We conducted semi-structured interviews with the patient, their next-of-kin and health professionals involved in the case. Within-case analysis identified barriers and facilitators in 4 phases (pre-hospital, presentation, transfer, in-hospital) followed by thematic analysis across cases using a case-study matrix. Results: Twenty-seven cases with 90 interviewees yielded five themes related to facilitators or barriers of timely treatment. "Early recognition" led to urgent response. "Accessibility to health care" depended on patient's location, transport, and environmental conditions. Good "Coordination" between and within health services was a key facilitator. "Complexity" of patient's condition affected time to treatment in multiple time periods. "Availability of resources" was identified most frequently during the diagnostic and treatment phases as both barrier and facilitator. Conclusions: The identified themes may be modifiable at the patient/health professional level and health system level and may improve timely treatment of aSAH through targeted interventions, subsequently contributing to improve morbidity and mortality of patients with aSAH.